Use the substitution method to solve:
m + t = 20
11m + 3t = 100
Check Format
Equation 1 is in the correct format.
Check Format
Equation 2 is in the correct format.
Rearrange Equation 2 to solve for m:
11m + 3t = 100
Subtract 3t from both sides to isolate m:
11m + 3t - 3t = 100 - 3t
11m = 100 - 3t
Now divide by 11:
Revised Equation 2:
Plug Revised Equation 2 value into m:
1(m) + t = 20
1 * ((100 - 3t)/11) + t = 20
((100 - 3t)/11) + t = 20
Multiply equation 1 through by 11
11 * (((100 - 3t)/11) + t = 20)
11 * (((100 - 3t)/11) + t = 20)
100 - 3t + 11t = 220
Group like terms:
-3t + 11t = 220 - 100
8t = 120
Divide each side by 8
t = 15
Plug this answer into Equation 1
1m + 1(15) = 20
1m + 15 = 20
1m = 20 - 15
1m = 5
Divide each side by 1
m = 5
Math is always fascinating! Have you noticed? On the path to discovering the ultimate
mysteries of math, we move forward with small steps.
Many such discoveries of mathematical formulas validate the research efforts of those who
came before us. If you want to inspire yourself and those around you, try making your own
Custom Enamel Badges of achievement for small accomplishments.
These vivid pin badges can be a constant reminder that numbers aren't exactly cold and that
they can always be accompanied by fun and hope.